Health information system linkage and coordination are critical for increasing access to secondary prevention in Aboriginal health: a qualitative study - Digiacomo, Michelle; Davidson, Patricia; Taylor, Katherine; Smith, J.; Dimer, L.; Ali, Mohammed; Wood, M.; Leahy, T.; Thompson, Sandra (Radcliffe Medical Press Ltd., 2010)
Background: Aboriginal Australians have low rates of participation in cardiac rehabilitation (CR), despite having high rates of cardiovascular disease. Barriers to CR participation reflect multiple patient-related issues. However, an examination of the broader context of health service delivery design and implementation is needed. Aims: To identify health professionals' perspectives of systems related barriers to implementation of the National Health and Medical Research Council (NHMRC) guidelines Strengthening Cardiac Rehabilitation and Secondary Prevention for Aboriginal and Torres Strait Islander Peoples. Method: Semi-structured interviews were conducted with health professionals involved in CR within mainstream and Aboriginal Community Controlled Health Services in Western Australia (WA). Thirty-eight health professionals from 17 services (ten rural, seven metropolitan) listed in the WA Directory of CR services and seven Aboriginal Medical Services in WA were interviewed.Results: Respondents reported barriers encountered in health information management and the impact of access to CR services for Aboriginal people. Crucial issues identified by participants were: poor communication across the health care sector and between providers, inconsistent and insufficient data collection processes (particularly relating to Aboriginal ethnicity identification), and challenges resulting from multiple clinical information systems and incompatible technologies. Conclusions: This study has demonstrated that inadequate information systems and communication strategies, particularly those representing the interface between primary and secondary care, contribute to the low participation rates of Aboriginal Australians in CR. Although these challenges are shared by non-Aboriginal Australians, the needs are greater for Aboriginal Australians and innovative solutions are required.